Asymmetric routes to pentadec-1-en-4-ol: application to the syntheses of aculeatins F and epi-F, (R)- and (S)-5-hexadecanolide and a formal synthesis of solenopsin - Harbindu, Anand; Sharma, Brijesh M.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2013)
A short and simple route to the synthesis of pentadec-1-en-4-ol, an important synthetic building block for the aculeatins F and epi-F, insect pheromone 5-hexadecanolide, solenopsin and various other natural products has been developed via proline-catalyzed alpha-aminoxylation of an aldehyde and hydrolytic kinetic resolution of a terminal epoxide. While the synthesis of aculeatins F and epi-F has been accomplished using a FIFA promoted oxidative spirocyclization/dithiane deprotection reaction sequence and linchpin coupling as key steps, the synthesis of hexadecanolide and a formal synthesis of solenopsin was performed using ring-closing metathesis (RCM) as key step. (C) 2013 Elsevier Ltd. All rights reserved.